2008
DOI: 10.1603/0046-225x(2008)37[938:crowst]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Web-Building Spiders to Deer Browsing Among Habitats and Feeding Guilds

Abstract: We examined web-building spider species richness and abundance in forests across a deer density gradient to determine the effects of sika deer browsing on spiders among habitats and feeding guilds. Deer decreased the abundance of web-building spiders in understory vegetation but increased their abundance in the litter layer. Deer seemed to affect web-building spiders in the understory vegetation by reducing the number of sites for webs because vegetation complexity was positively correlated with spider density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…, Takada et al. ). Differences in species richness response could result from overall habitat differences, specific metrics for estimating structure, and ecological differences in cervid behavior.…”
Section: Discussionmentioning
confidence: 98%
“…, Takada et al. ). Differences in species richness response could result from overall habitat differences, specific metrics for estimating structure, and ecological differences in cervid behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Increases in abundance and species diversity were the main focus of interactions with invertebrates. These highlighted changes in community structure between predator and prey groups as an indirect result of the presence of engineer species (Takada, Baba, Yanagi, Terada, & Miyashita, ). Engineer interactions with plants and plant communities induced a range of reliable secondary responses in biomass or cover associated with impacts on soil nutrient and physical properties (8% of interactions).…”
Section: Which Species Act As Ecosystem Engineers and With Whom Do Thmentioning
confidence: 99%
“…Deer density has been estimated to a resolution of 1 km 2 using distribution patterns of faecal pellet densities (see Appendix S1 in Supporting Information). Our previous studies revealed that the estimated density in a 1 km 9 1 km grid provides a good explanation of the impact of deer on biological communities and agricultural crops (Suzuki et al , 2013Takada et al 2008Takada et al , 2010Takagi & Miyashita 2012; see also S1 in Miyashita et al 2008).…”
Section: Introductionmentioning
confidence: 93%